Correlation between pubic hair grooming and STIs: results from a nationally representative probability sample. (5th December 2016) - Osterberg, E Charles; Gaither, Thomas W; Awad, Mohannad A; Truesdale, Matthew D; Allen, Isabel; Sutcliffe, Siobhan; Breyer, Benjamin N
Abstract : Objective: STIs are the most common infections among adults. Concurrently, pubic hair grooming is prevalent. Small-scale studies have demonstrated a relationship between pubic hair grooming and STIs. We aim to examine this relationship in a large sample of men and women. Design: We conducted a probability survey of US residents aged 18–65 years. The survey ascertained self-reported pubic hair grooming practices, sexual behaviours and STI history. We defined extreme grooming as removal of all pubic hair more than 11 times per year and high-frequency grooming as daily/weekly trimming. Cutaneous STIs included herpes, human papillomavirus, syphilis and molluscum. Secretory STIs included gonorrhoea, chlamydia and HIV. We analysed lice separately. Results: Of 7580 respondents who completed the survey, 74% reported grooming their pubic hair, 66% of men and 84% of women. After adjusting for age and lifetime sexual partners, ever having groomed was positively associated with a history of self-reported STIs (OR 1.8; 95% CI 1.4 to 2.2), including cutaneous STIs (OR 2.6; CI 1.8 to 3.7), secretory STIs (OR 1.7; CI 1.3 to 2.2) and lice (OR 1.9; CI 1.3 to 2.9). These positive associations were stronger for extreme groomers (OR 4.4; CI 2.9 to 6.8) and high-frequency groomers (OR 3.5; CI 2.3 to 5.4) with cutaneous STIs, and for non-extreme groomers (OR 2.0; CI 1.3 to 3.0) and low-frequency groomers (OR 2.0; CI 1.3 to 3.1) with lice. Conclusions: Among a representative sample of US residents, pubic hair grooming was positively related to self-reported STI history. Further research is warranted to gain insight into STI risk-reduction strategies.